Răspuns :
[tex]a)2 \sqrt{3} x - \sqrt{3} = 0[/tex]
[tex]2 \sqrt{3} x = \sqrt{3} \: | \div \sqrt{3} [/tex]
[tex]2x = 1[/tex]
[tex]x = \frac{1}{2} [/tex]
[tex]b)( \sqrt{5} + 1) \times x = 1 + \sqrt{5} [/tex]
[tex]( \sqrt{5} + 1) \times x = \sqrt{5} + 1 \: | \div ( \sqrt{5} + 1)[/tex]
[tex]x = 1[/tex]
[tex]c)6 = x - 0.5[/tex]
[tex]x = 6 + 0.5[/tex]
[tex]x = 6.5[/tex]
[tex]d)3 \sqrt{2} = x + 2 \sqrt{2} [/tex]
[tex]x = 3 \sqrt{2} - 2 \sqrt{2} [/tex]
[tex]x = \sqrt{2} [/tex]
[tex]e)0.(5) = \frac{5}{9} - x[/tex]
[tex] \frac{5}{9} = \frac{5}{9} - x[/tex]
[tex] - x = \frac{5}{9} - \frac{5}{9} [/tex]
[tex] - x = 0[/tex]
[tex]x = 0[/tex]
[tex]2 \sqrt{3} x = \sqrt{3} \: | \div \sqrt{3} [/tex]
[tex]2x = 1[/tex]
[tex]x = \frac{1}{2} [/tex]
[tex]b)( \sqrt{5} + 1) \times x = 1 + \sqrt{5} [/tex]
[tex]( \sqrt{5} + 1) \times x = \sqrt{5} + 1 \: | \div ( \sqrt{5} + 1)[/tex]
[tex]x = 1[/tex]
[tex]c)6 = x - 0.5[/tex]
[tex]x = 6 + 0.5[/tex]
[tex]x = 6.5[/tex]
[tex]d)3 \sqrt{2} = x + 2 \sqrt{2} [/tex]
[tex]x = 3 \sqrt{2} - 2 \sqrt{2} [/tex]
[tex]x = \sqrt{2} [/tex]
[tex]e)0.(5) = \frac{5}{9} - x[/tex]
[tex] \frac{5}{9} = \frac{5}{9} - x[/tex]
[tex] - x = \frac{5}{9} - \frac{5}{9} [/tex]
[tex] - x = 0[/tex]
[tex]x = 0[/tex]